REFORMING THE ALTERNATIVE MECHANISMS OF DISPUTE RESOLUTION IN PAKISTAN - Ahsan Iqbal; Muhammad Waqar; Saqib Shahbaz; Syed Shiar Abbas; Nafees Ahmed khan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
Alternate Dispute Resolution (ADR) is paradigm method to settle disputes in cost efficient, time effective, and win-win manner beyond the traditional system. Pakistan has Alternate Dispute Resolution laws in place, which gives breathing space to resolve dispute outside the court room, however, lamentably its inept is due to multiple aspects such as unawareness at receiving end, absence of infrastructure and most importantly, in its comprehension, it is not a substitute to traditional judicial system but to support the judicial system. Pakistan is in developing phase in terms of implementation and acceptability to strengthen the process of Alternate Dispute Resolution in the Country. This study aims to analyze applicable laws in Pakistan for ADR to resolve dispute at national and international level, further, which put forth various reforms, including, awareness, strengthen the mechanism of implementation, infrastructure development, research and role of judiciary to make ADR process worthwhile, effectual and user-friendly, and to build the user trust on ADR system in the genre of written discussion.